Anthropometric, functional and foot trajectory determinants of stride length in self-reliant community-dwelling elderly persons in Talca, Chile - González,Paul Medina (2016)
Abstract Objective: To analyze anthropometric, muscle performance and foot trajectory determinants of stride length (SL) during walking at a comfortable pace among self-reliant community-dwelling elderly persons in Talca, Chile. Method: A total of 63 self-reliant elderly persons participated in this observational and cross-sectional study. They were characterized by the anthropometric measures of mass, height and body mass index. Dorsiflexor muscle strength performance (DF-MS) and rate of force development were quantified. Finally, the elderly persons were asked to walk comfortably around a 40 meter elliptical circuit, using determined SL and maximum foot clearance (MaxFC) and minimum foot clearance (MFC) trajectory parameters. The SL determinants were evaluated by calculating the coefficient of determination (r2) considering a level of significance of p≤0.05. Results: The anthropometric variables demonstrated significant correlations (r>0.41) with the explanation of SL remaining incipient (r2<0.20). Muscle performance, meanwhile, was significantly correlated (r>0.52), with DF-MS standing out (r2=0.342). MaxFC represented a significant explanation for the data (r2=0.396), while the low correlation of MFC was not significant (r=0.24, r2=0.058). Conclusion: MaxFC and DF-MS are determinants of SL in self-reliant elderly Chileans. It is proposed that gait parameters could be normalized in accordance with trajectory and muscular performance.